Flow-Diversion for Complex Posterior Communicating Artery Aneurysms Associated with a Fetal Posterior Circulation. (16th November 2020) - Baranoski, Jacob F; Merrill, Sarah; Hendricks, Benjamin K; Catapano, Joshua; Cole, Tyler S; Majmundar, Neil J; Wilkinson, D. Andrew; Albuquerque, Felipe; Ducruet, Andrew F
Abstract: INTRODUCTION: Flow-diverting stents (FDS) are effective in treating complex intracranial aneurysms including posterior communicating artery (PCoA) aneurysms. However, some studies have suggested limited efficacy of FDS for PCoA aneurysms associated with a fetal PCoA (FPCoA). METHODS: We performed a retrospective analysis from 1/2012 to 12/2018 to identify patients with FPCoA aneurysms treated using a FDS as the standalone intervention. We identified aneurysms where the FPCoA vessel originated from the neck/dome of the aneurysm and were therefore not appropriate for standard coil embolization. We considered a FPCoA as any PCoA with a caliber larger than the P1 segment of the PCA. RESULTS: We performed stand-alone, single device, FDS treatments for 16 PCoA aneurysms associated with a FPCoA vessel that originated from either the neck or dome of the aneurysm. Ten were previously treated and the FDS was used to treat a recurrence/residual. Seven were previously ruptured. We sized the device to ensure excellent wall apposition and focused on device expansion into the aneurysm neck to optimize flow-diversion. We achieved an excellent angiographic result in 12 of the 16 cases (75%), with complete obliteration of the aneurysm in 10 cases (62.5%) and near complete obliteration with only trace filling of a neochannel at the aneurysm base in 2 (12.5%). In the remaining 4 cases, in whom follow-up is ongoing, we observed significant, progressive aneurysm occlusion with marked flow stagnation. No cases necessitated additional treatment. We assessed FPCoA patency on follow-up and observed complete patency in 9, decreased flow in 4, markedly diminished flow in 2, and FPCoA occlusion in 1 patient. In all 7 cases with decreased FPCoA flow, we noted co-incident increased P1 flow. No patient developed posterior circulation ischemia. No procedural complications were encountered. Mean follow-up was 19.9 months. CONCLUSION: FDS can be a safe and effective treatment option for PCoA aneurysms despite the presence of a FPCoA and may be of particular utility for complex FPCoA aneurysms where standard coiling or microsurgical treatment is limited. Maximizing device expansion across the aneurysm neck may contribute to successful outcomes.